Stop the LVAD bleeding - Koliopoulou, Antigone; Selzman, Craig H. (Journal of Thoracic Disease, 2017)
Among the therapeutic options available for patient with advanced heart failure, left ventricular assist devices (LVAD) are a safe and durable option as bridge to transplantation or as destination therapy. Despite improving survival and quality of life, nonsurgical bleeding—manifesting as epistaxis, gastrointestinal bleeding, and hemorrhagic strokes—contribute to plague this group of patients and is a major cause of both morbidity and mortality and contributes to a significant socioeconomic burden. While much has been made of shear forces, breakdown of von Willebrand polymers, and anticoagulation regimens, little has changed with respect to LVAD-related bleeding complications. As such, much interest exists to identify biomarkers that could not only predict these events but that could also inform potential therapeutic targets.